Reconstruction of production and heating boiler plant JSC "NP NC KBK IM. S.P. Titov" with building expansion - A. Sh. Nizamova; Yu. V. Abasev (Известия высших учебных заведений: Проблемы энергетики)
RELEVANCE. In Russia there are a large number of large and small boiler houses that supply steam and hot water to industrial enterprises. Today, more than 70% of boiler houses require serious modernization, the options for which can be different. Research into the area of modernization and reconstruction of boiler houses in the country is important, since most of the equipment has exhausted its service life, and the need for heat supply is increasing due to the increase in industrial output.   TARGET. Consideration of one of the options for modernization and reconstruction of a specific boiler house.   METHODS. When considering the option, the steam-water heating boiler developed by the Taganrog Boiler Plant and well-known methods for expanding energy enterprises were taken as the basis.   RESULTS. The article describes the relevance of the topic, presents an option for modernizing a hot water boiler, which makes it possible to operate the boiler in a combined mode, which allows solving steam reserve issues in the short term, and also presents an option for expanding the boiler room.   CONCLUSIONS. The option of reconstructing and modernizing an industrial heating boiler house with its expansion and transfer of hot water boilers to steam mode is an opportunity to solve the growing production need for process steam.